1990
DOI: 10.2190/2p3j-a9ah-hhf4-00rg
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers for Alzheimer's Patients: What We Are Learning from Research

Abstract: The research literature on adjustment by family members to providing care to victims of Alzheimer's disease is new and expanding rapidly. The purpose of this review is to summarize the categories and methods of that research; to evaluate critically the state of knowledge these studies are producing; and to suggest ways of strengthening future investigations. The review is organized around psychological, social, and health factors as antecedents or correlates of similar categories of outcomes for caregivers. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
2
9

Year Published

1993
1993
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(55 citation statements)
references
References 24 publications
0
42
2
9
Order By: Relevance
“…Inconsistent with some previous studies, we found that female caregivers who performed more personal care tasks, such as toileting and bathing, as well as more household chores, did not show a relationship between perceived burden and caregiver's gender [13,30] . In addition, our results indicate that caregiver level of education appeared to have some relationship with perceived burden [13,30] and HRQL [13] , with a worsening of both, level of burden and HRQL, with lower levels of caregiver education.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Inconsistent with some previous studies, we found that female caregivers who performed more personal care tasks, such as toileting and bathing, as well as more household chores, did not show a relationship between perceived burden and caregiver's gender [13,30] . In addition, our results indicate that caregiver level of education appeared to have some relationship with perceived burden [13,30] and HRQL [13] , with a worsening of both, level of burden and HRQL, with lower levels of caregiver education.…”
Section: Discussioncontrasting
confidence: 52%
“…In addition, our results indicate that caregiver level of education appeared to have some relationship with perceived burden [13,30] and HRQL [13] , with a worsening of both, level of burden and HRQL, with lower levels of caregiver education. This might be due to the fact that more highly educated caregivers have more realistic expectations about the course of the disease as well as better social and financial support and, therefore, can adapt better to the stress and changing care needs of the person with AD.…”
Section: Discussionmentioning
confidence: 57%
“…There is substantial evidence in the literature that female caregivers, and daughters in particular, experience more stress than male caregivers [35,38], although not all studies report clear-cut gender differences [24]. In the present study the high-burden group included a majority of daughters.…”
Section: Discussionmentioning
confidence: 82%
“…The Zarit Burden Interview (BI) continues to be widely used in the study of caregiver burden [16,[23][24][25][26]. Various forms exist.…”
Section: Caregiver Variablesmentioning
confidence: 99%
“…Fuente: Trabajo de investigación 5 (2) 7 (2,8) 25 (9,9) 136 (54) 32 (12,7) 146 (57,9) Se logró evidenciar que el grado de sobrecarga en el cuidador es independiente de su nivel de escolaridad, sin embargo, se observó que a menor nivel de escolaridad mayor grado de sobrecarga (Tau C Kendall = -0.024). En el estudio de Ocampo, Herrera y Torres (22), se encontró asociación estadística significativa con respeto al grado de escolaridad siendo contradictorio con lo obtenido en el estudio donde no se encontró asociación de sobrecarga con esta variable demográfica.…”
Section: Tabla 3 a Asociación Del Nivel De Escolaridad Con El Nivel unclassified